Rosyjska szkoła gramatyki funkcjonalnej: postulaty, kierunki, ludzie - Kiklewicz, Aleksander (Przegląd Rusycystyczny, 2009)
THE RUSSIAN SCHOOL OF FUNCTIONAL GRAMMAR: POSTULATES, DIRECTIONS, PERSONAL REFERENCES Summary The study concentrates on the functional bases of the linguistic theory of a language. The author discusses the current directions of functional investigations in Russian linguistics, namely the conceptions by A.V. Bondarko, M.A. Šeljakin, M.I. Otkupščikova, G.A. Zolotova, M.V. Vsevolodova, Z.L. Novoženova, A.A. Kamalova. Such categories of functional grammar are in centre of attention, as the functional-semantic fi eld, the functional class, the continuative character of language system, the nominative vs. semantic approach in the functional grammar and other. Moreover the author considers the functional classifi cation of part of speech, as well so the completion of grammatical description with the information about the cultural background of grammatical forms of language. ROSYJSKA SZKOŁA GRAMATYKI FUNKCJONALNEJ: POSTULATY, KIERUNKI, LUDZIE Streszczenie Niniejszy artykuł jest poświęcony funkcjonalnym podstawom lingwistycznej teorii języka. Autor omawia bieżące kierunki funkcjonalnych badań w językoznawstwie rosyjskim, a mianowicie koncepcje takich badaczy jak A.W. Bondarko, M.A. Szeljakin, M.I. Otkupszczikowa, G.A. Zołotowa, M.W. Wsiewołodowa, Z.L. Novożenova, A.A. Ka-małowa. Kategorie gramatyki funkcjonalnej, znajdujące się w centrum uwagi, to pole funkcjonalno-semantyczne, klasa funkcjonalna, ciągły charakter systemu językowego, nominatywne a semantyczne podejście w gramatyce funkcjonalnej oraz inne. Ponadto, autor rozważa funkcjonalną klasyfi kację części mowy, jak i uzupełnienie opisu gramatycznego informacją o tle kulturowym form gramatycznych języka.